Teacher's Efforts in Improving Traditional Dance Art Typical of Malang in Extracurricular Class V Elementary School - Hadiyani, Vino Putra (Jurnal Ilmiah Iqra', 2024)
This research was conducted to describe the extracurricular learning activities of typical Malang dance. In art learning, of course, it is necessary to plan and implement teacher efforts so as to create teaching and learning activities carried out at Mojorejo 01 Batu public elementary school. This research uses a descriptive qualitative method with the aim of knowing the extracurricular activities of typical unfortunate dance, Interviews were conducted in a relaxed and unscheduled manner, the aim was to dig deeper into reactions and responses that were more straightforward and natural. The results of this study are the teacher's efforts to improve typical unfortunate dance arts in extracurricular activities carried out at Mojorejo 01 Batu elementary school and the implementation that goes well given a lot of support from teachers as facilitators and educators, of course, has a good impact on KBM learning (Teaching and Learning Activities) also has a positive impact on students in learning activities carried out with dance movement activities and makes pride in the typical art of the region, namely the art of unfortunate dance.